Efforts to Increase Creativity in 5-6 Year Old Children through the Use of Illustrated Story Media at RA Nurul Hidayah - Sugiharti, Upit (Jurnal Profesi Guru Indonesia, 2024)
This study aims to improve the creativity of children aged 5-6 years through illustrated story media at RA Nurul Hidayah, Kebun Dalam Village. Creativity is an important aspect in early childhood development that can be encouraged through appropriate stimulation, one of which is through illustrated story media. The research method used is classroom action research (CAR) with a qualitative and quantitative approach. Data were collected through observation, interviews, and documentation. The results of the study showed that the use of illustrated stories effectively increased children's creativity in various aspects, such as imaginative thinking skills, verbal expression, and drawing skills. Thus, illustrated story media can be an interesting and effective learning alternative in developing early childhood creativity.